2008
DOI: 10.1021/ma8020823
|View full text |Cite
|
Sign up to set email alerts
|

Grignard Metathesis Method (GRIM): Toward a Universal Method for the Synthesis of Conjugated Polymers

Abstract: Materials. Lithium chloride, lithium t-butoxide, isopropyl magnesium chloride (2M in THF), t-butyl magnesium chloride (2M in diethyl ether), n-butyl magnesium chloride (2M in THF), n-butyl lithium (1.6 M in hexane), and 9,9-dioctyl-2,7-dibromofluorene were purchased from Aldrich and used as received. Tetrahydrofuran was distilled from sodium benzophenone ketyl and collected over molecular sieves. n-Bu 3 MgLi was synthesized in anhydrous toluene at -10 0 C as previously reported.Synthesis of RMgCl.LiX (R = i-Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
159
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(167 citation statements)
references
References 23 publications
7
159
0
1
Order By: Relevance
“…58,88,89 Metal-catalyzed cross-couplings are another method for producing conjugated polymers. [90][91][92][93][94] Unlike oxidative synthesis, polymers synthesized in this way are formed in a charge-neutral state. Unfortunately, these systems can sometimes require the presence of specific functional groups and sensitive reaction conditions not conducive to producing large quantities of material suitable for electrodes.…”
Section: Synthesismentioning
confidence: 99%
“…58,88,89 Metal-catalyzed cross-couplings are another method for producing conjugated polymers. [90][91][92][93][94] Unlike oxidative synthesis, polymers synthesized in this way are formed in a charge-neutral state. Unfortunately, these systems can sometimes require the presence of specific functional groups and sensitive reaction conditions not conducive to producing large quantities of material suitable for electrodes.…”
Section: Synthesismentioning
confidence: 99%
“…This problem has been reported for other polymers, such as poly(9,9-dioctyfluorene). 49 In that case, the use of the magnesium complex [tBuMgCl·LiCl·15-crown-5] as the metallating species prevented any further substitution most likely because the tert-butyl cation is more stable compared to isopropyl cation. Treatment of 4 with 1 equiv of [tBuMgCl·LiCl·15-crown-5] at 20 °C for 10 min in THF gave 7 (100% yield based on analytical GC-MS with analysis of the protonated species 3).…”
Section: Synthesis Of Poly(thiophene-alt-pyrrole) (Ptp) Withmentioning
confidence: 99%
“…However, it was found that yields of this series of copolymer were relatively low. Hence, it is suggested that for the synthesis of this series of copolymers, other Grignard regents such as isopropylmagnesium chloride (i-PrMgCl) or isopropylmagnesium bromide (i-PrMgBr) together with lithium chloride (LiCl) may be used to afford the copolymers in good yields [29,30]. Since the copolymer synthesized by Wei's group comprising of equal molar ratio of M1!…”
Section: Instrumentationmentioning
confidence: 99%